Upacara Biyukukung (Kearifan Lokal Masyarakat Bali dalam Menjaga Teo-Agrikultur) - Suastini, Ni Nyoman (Institut Hindu Dharma Denpasar, 2021)
Biyukukung ceremony was carried out by Balinese people who worked in agriculture, especially rice farming. This ceremony was related with Balinese peopleâ€™s effort religiously to gained prosperity for their rice in the field. As a rice farmer, Balinese people often had adversity in their field, liked damaged by pests, lacked of water, and more. As a religious people, they used this ceremony to avoid any adversity. Biyukukung ceremony was carried out by farmers, started from prepared the facilities like banten and other which related with the ceremony. The meaning of this ceremony was an expression of farmersâ€™ thankful to God in the form of his manifestation as Dewi Sri and Dewa Wisnu which provided safety and growth the rice fertilely, protected from the pests, and other damaged. That was why Balinese people carried out the ceremony which had inherited by every generation. This ceremony also made different meaning of agriculture group, which was not only about farming. Moreover, the mean was combined the concept of Hinduâ€™s theology and farming. This tradition then became a unified in farming system, so that the religion ceremony and farming activity be related to each other. Balinese people always depended to God for their safety, so that all of their action, included farming, was related. This relation made Bali unique, there was no line between religion and culture in their daily life. Thus, â€œBiyukukung Ceremonyâ€ had function and meaning to prayed the rice growth fertilely and also the field safety, so that the farmers could harvest well according to their expectation